Studi Etnobotani Tanaman Mustajab (Abelmoschus manihot) sebagai Antipiretik Alami Berdasarkan Pengetahuan Tradisional Masyarakat RW 08, Desa Sindangsari, Garut - Moch.Naufal Ramdhani; Feby Nurul Asri Maharani; Habib Zikri; Tri Cahyanto (Hidroponik : Jurnal Ilmu Pertanian Dan Teknologi Dalam Ilmu Tanaman, 2025)
Garut is one of the areas that has local cultural wisdom that is still beautiful and preserved. The diversity of existing plants has sufficient economic value and has potential as alternative ingredients and medicines. The people of Garut still cultivate and use plants as alternative medicines that can cure various diseases. The Mustajab plant or Gedi Leaf with the scientific name Abelmoschus manihot of the Malvace family is one of the herbal plants that has long been used by the people of Sindangsari village as a fever reducer or pyretic in babies. Pyretics is a condition in which the body experiences an increase in temperature above normal limits due to a response to infection or inflammation. This research was conducted in Sindangsari Village, Leuwigoong District, Garut Regency. The method used in this research is an exploratory survey method. The data collection technique uses a purposive sampling method. This research data analysis uses qualitative and quantitative methods. To calculate the use value, the UV method is used. Apart from that, the Fidelity Level Index (FLI) method is also used. Mustajab leaves are included in the category of plants with metabolite compounds which can produce compounds from the soil itself. Mustajab leaves can cure fever in babies because they contain many active compounds, one of which is flavonoid compounds. Based on the results presented in the table, it can be seen that the highest FL value is in the mustajab plant which is used as a treatment for fever in babies with a FL value of 51.5%. Based on the results table, it can be seen that the highest UV value is in the use of mustajab leaves as a medicine for baby fever with a UV value of 0.51. There are many processing and application methods for using mustajab leaves as traditional medicine, including boiling, squeezing and pounding. Based on the data above, it can be concluded that mustajab leaves are one of the traditional food plants which are usually used by rural communities as an alternative medicine to reduce fever in babies.